WOMEN IN ENGINEERING: KAJIAN TENTANG RELASI GENDER DI SEKOLAH MENENGAH KEJURUAN BIDANG KEAHLIAN TEKNIK - Rifki Ardian Firdaus, - (2021)
ABSTRAK The purpose of this study was to determine gender relations in Vocational Schools (SMK) with the Business and Motorcycle Engineering Study Program (TBSM). The informants in this study were 14 students of class XII. The objectives of this study were (1) to determine the background of student study program selection (male and female); (2) Knowing the views of male and female students in the Business and Motorcycle Engineering Study Program; (3) Knowing gender responsiveness in the learning process in the Business and Motorcycle Engineering Study Program. The research was conducted at SMK N 4 Sukabumi City. Using FGD (Focus Group Discussion), personal interviews and observations. Research shows that there is still a lack of student knowledge, parental direction and direction from the teacher in making the selection to continue education, especially continuing to vocational high schools in engineering. Knowing students 'interests and talents, encouragement from parents and the influence of the environment make it important to improve students' abilities in carrying out both theoretical and practical learning. The labeling of male students towards women in learning at SMK with the Department of Motorbike Engineering and Business, the lack of toilet facilities for women is the finding of this study and is a problem that needs to be resolved in vocational education in the field of Business and Motorcycle Engineering expertise. Keywords: Students, views, women, responsiveness